2012
DOI: 10.1029/2012gl053540
|View full text |Cite
|
Sign up to set email alerts
|

P‐V‐T equation of state for ε‐iron up to 80 GPa and 1900 K using the Kawai‐type high pressure apparatus equipped with sintered diamond anvils

Abstract: [1] In order to determine the P-V-T equation of state of ɛ-iron, in situ X-ray observations were carried out at pressures up to 80 GPa and temperatures up to 1900 K using the Kawai-type high pressure apparatus equipped with sintered diamond anvils which was interfaced with synchrotron radiation. The present results indicate the unit cell volume at ambient conditions V 0 = 22.15(5) Å 3 , the isothermal bulk modulus K T0 = 202(7) GPa and its pressure derivative K′ T0 = 4.5(2), the Debye temperature q 0 = 1173(62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…Comparison of seismic observation with experimental data has shown that the density of the core is less than that of pure iron, known as the density deficit [Birch, 1952]. Compression of hcp-Fe has been extensively studied to multi-megabar pressures to better constrain the density of iron at core pressures [Mao et al, 1990;Dubrovinsky et al, 2000;Dewaele et al, 2006;Yamazaki et al, 2012;Sakai et al, 2014]. This value is then used to determine the contributions of Ni and light elements to the density of the core.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of seismic observation with experimental data has shown that the density of the core is less than that of pure iron, known as the density deficit [Birch, 1952]. Compression of hcp-Fe has been extensively studied to multi-megabar pressures to better constrain the density of iron at core pressures [Mao et al, 1990;Dubrovinsky et al, 2000;Dewaele et al, 2006;Yamazaki et al, 2012;Sakai et al, 2014]. This value is then used to determine the contributions of Ni and light elements to the density of the core.…”
Section: Introductionmentioning
confidence: 99%
“…Dewaele et al [2006] determined the room temperature compression curve of iron under quasi-hydrostatic conditions using helium (He) (up to 197 GPa) and neon (Ne) (up to 205 GPa) as the pressure-transmitting media. More recently, Yamazaki et al [2012] obtained compression data of iron up to 80 GPa in the multianvil apparatus using gold (Au) as the pressure standard, and Sakai et al [2014] performed the compression experiment in the diamond anvil cell up to 280 GPa using NaCl as the pressure standard. More recently, Yamazaki et al [2012] obtained compression data of iron up to 80 GPa in the multianvil apparatus using gold (Au) as the pressure standard, and Sakai et al [2014] performed the compression experiment in the diamond anvil cell up to 280 GPa using NaCl as the pressure standard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent estimations for the core density deficit are still approximately the same as those proposed by Birch []. The density deficits vary from 5 to 12% for the outer core [ Stevenson , ; Anderson and Isaak , ] and from 3 to 5% for the inner core [ Stixrude et al ., ; Dubrovinsky et al ., ; Komabayashi and Fei , ; Yamazaki et al ., ]. In addition to the density deficit, the core has lower sound velocities with respect to pure iron, which also provides evidence for light element addition [ Fiquet et al ., ; Lin et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…During the last several years, a significant amount of new P–V–T data for fcc-Fe and hcp-Fe, especially at very high temperatures, have appeared61325262728 and, in addition, the melting curve of Fe was shifted to higher temperatures according to measurements in ref. 14.…”
mentioning
confidence: 99%